IMPLEMENTASI NILAI KARAKTER DISIPLIN, KREATIF DAN TANGGUNG JAWAB MELALUI PAIKEM DI SDN 58 TOLONG KECAMATAN SENGAH TEMILAKABUPATEN LANDAK - Elly Andriani A; Sulistyarini Sulistyarini; Antonius Totok Priyadi (Universitas Tanjungpura, 2022)
This study aims to describe the implementation of disciplinary, creative andresponsibility characters through PAIKEM in class III SDN 58 TOLONGLandak. The formulation of the problem described in this study is how theteacher's planning for learning with PAIKEM, teacher implementation ofPAIKEM learning, the results of the integration of students' discipline,creative and responsibility characters after studying with PAIKEM,obstacles encountered in the implementation of PAIKEM and efforts toovercome obstacles and results learn students through PAIKEM. Thisresearch is a descriptive research with a qualitative approach. The subjectsin this study were principal, teacher, and students. Data collection wascarried out through observation, interviews, and documentation. Dataanalysis was carried out in stages: data reduction, data display, anddrawing conclusions. The technique of checking the validity of the data usedtriangulation. The results showed that the character of discipline, creativity,and responsibility through integrated PAIKEM at the planning,implementation, and evaluation stages of learning had been carried out bythe teacher. The implementation of learning by applying the character ofdiscipline, creativity and responsibility is carried out by the teacher byapplying PAIKEM which is carried out through the example of the teacherand habituation activities carried out every day, so that it can build thecharacter of students towards a better direction, with continuous guidanceand motivation from the teacher.Keywords: Discipline, Creative, Responsibility, PAIKEM